Exploring the Cocrystal of Aspirin: A Pathway to Enhanced Pharmaceutical Efficacy - Ankita S. Patil; Sujata A. Jadhav; Amol S. Shete; Swapnil D.Patil (International Journal of Medical Toxicology and Legal Medicine, 2024)
The development of cocrystals has emerged as a promising approach in pharmaceutical research to address challenges associated with the physicochemical properties of active pharmaceutical ingredients (APIs). This study focuses on exploring the cocrystal of aspirin, a widely used nonsteroidal anti-inflammatory drug (NSAID), to enhance its pharmaceutical efficacy. Aspirin is known for its analgesic, antipyretic, and antiinflammatory properties, but its limited aqueous solubility and potential gastrointestinal side effects present significant limitations. By employing cocrystallization techniques, this research aims to improve the solubility, stability, and bioavailability of aspirin without altering its pharmacological properties. A thorough literature review was conducted to understand the mechanisms of cocrystal formation and identify suitable coformers. Experimental studies were performed using solvent evaporation and grinding methods to synthesize aspirin cocrystals. The resulting cocrystals were characterized using techniques such as powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), and Fourier-transform infrared spectroscopy (FTIR). Preliminary findings demonstrate that aspirin cocrystals exhibit enhanced aqueous solubility and improved dissolution rates compared to pure aspirin. These improvements have the potential to reduce dosage requirements and minimize adverse effects, thereby increasing patient compliance and therapeutic outcomes. Furthermore, this study highlights the broader applicability of cocrystallization for other poorly soluble drugs, offering a cost-effective and scalable pathway for pharmaceutical advancements.